Wayang Purwa dalam Kehidupan Masyarakat Jawa - Bikuwata, Bikuwata (Jurnal Masyarakat dan Budaya, 1999)
The Media of Wayang Purwa and Macapat had been used by the Walls when they socialized the religion of Islam in Java. After the establishment of Javanese culture, although its function as medium still has been existing till now.